Physical activity and cancer - Blake, Holly; Tennyson, R. (Nova Science, 2012)
It is widely accepted that physical activity is important for physical functioning and well-being, and as such the promotion of active lifestyles is becoming increasingly significant in public health policy both in the UK and worldwide. Sedentary lifestyles have been associated with increased risk of obesity and preventable disease including diabetes, coronary heart disease and some cancers. With regards cancer specifically, this chapter will provide a brief overview on current opinions on the link between physical activity and cancer prevention. The published evidence focuses both on primary and secondary prevention. More recent evidence has investigated the use of physical activity in secondary prevention for those who have been diagnosed with cancer and proposed a link between physical activity, morbidity and mortality in those with cancer. The evidence-base for secondary prevention is more limited. Nevertheless, studies to date have indicated that physical activity can improve both physical functioning and psychological outcomes in cancer survivors, and significantly improve quality of life. The exact nature of those interventions which confer the most positive effects is less well-established, and there is a current lack of consensus on the most appropriate type, intensity and duration of activity for people with cancer. It has not yet been well established as to which stage of the treatment programme physical activity should be encouraged (during or following treatment) or the most appropriate length of time during which structured physical activity interventions should be delivered to achieve beneficial results. These factors will be discussed in this chapter, and barriers to engaging in physical activity for those with a diagnosis of cancer will be considered. The chapter will conclude with a summary of key findings and the potential for further research.